UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS 5A SDN DUKUH KUPANG II SURABAYA MELALUI PBL MATERI BAGAIMANA BENTUK INDONESIAKU BERBANTUAN MEDIA DIGITAL ARCGIS - Juang Laksono, Galih; Susiloningsih, Wahyu; Sutarti; Darsono; Romadhoni, Achmad Eka; Farichah, Auliya Niswatul; Prahastowo, Bintang Apriyan; Fadilla, Fatma Nur; Saputra, Feri Candra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the learning motivation of 5A grade students at SDN DUKUH KUPANG II SURABAYA through the implementation of the Problem Based Learning (PBL) model in the subject "How is the Shape of My Indonesia," supported by the digital media ArcGIS. The background of this research is the low student motivation in understanding abstract and less contextual geographical material. The method used is Classroom Action Research (CAR), conducted in two cycles consisting of planning, action, observation, and reflection. Data were collected using questionnaires, observations, and interviews. The results showed that the implementation of PBL assisted by ArcGIS significantly enhanced students’ learning motivation. In cycle I, the average motivation level was 68%, which increased to 85% in cycle II. Student engagement in discussions also increased from 65% to 82%. These findings indicate that PBL combined with digital media can create active, enjoyable, and meaningful learning experiences, and is therefore recommended as an innovative approach to thematic learning in primary schools.